Peran Local Guide dalam Meningkatkan Pengalaman Wisata di Keraton Yogyakarta - Nofa Damayanti; Na’umi Berliana; Saptin Dwi Setyo; Apriasnita Siswani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the role of local guides in enhancing the tourist experience at Keraton Yogyakarta. Using a descriptive qualitative approach, data were obtained through in-depth interviews with local guides and direct observation of tour guiding activities. The results of the study indicate that local guides play an important role in conveying Javanese cultural, historical, and philosophical values ​​to tourists, as well as being a bridge in overcoming communication challenges, especially those related to foreign languages ​​and limited use of technology. Local guides are able to bring historical and cultural stories to life through a communicative and interactive approach, thereby increasing the emotional involvement of tourists. However, this study found that limitations in mastery of foreign languages ​​and the use of digital technology are still obstacles in efforts to optimally improve tourist understanding and satisfaction. Therefore, this study recommends the importance of developing ongoing training to improve language competence, communication skills, and adaptation to information technology to support the professionalism of local guides in the future.